Testing the thresholds of toxicological concern values using a new database for food-related substances. (10th October 2019) - Reilly, Linda; Serafimova, Rositsa; Partosch, Falko; Gundert-Remy, Ursula; Cortiñas Abrahantes, José; Dorne, Jean-Lou M.C.; Kass, George E.N.
Highlights: The TTC concept was tested on substances relevant to food safety. The threshold values for Cramer Classes I and III substances were comparable to the original Munro threshold values. Comparison with the GHS classification confirmed Cramer classification is conservative for substances relevant to food safety. This confirms the applicability of the TTC values to substances relevant to food safety. Abstract: The Threshold of Toxicological Concern (TTC) concept integrates data on exposure, chemical structure, toxicity and metabolism to identify a safe exposure threshold value for chemicals with insufficient toxicity data for risk assessment. The TTC values were originally derived from a non-cancer dataset of 613 compounds with a potentially small domain of applicability. There is interest to test whether the TTC values are applicable to a broader range of substances, particularly relevant to food safety using EFSA's new OpenFoodTox database. After exclusion of genotoxic compounds, organophosphates or carbamates or those belonging to the TTC exclusion categories, the remaining 329 substances in the EFSA OpenFoodTox database were categorized under the Cramer decision tree, into low (Class I), moderate (II), or high (III) toxicity profile. For Cramer Classes I and III the threshold values were 1000 μg/person per day (90% confidence interval: 187–2190) and 87 μg/person per day (90% confidence interval: 60–153), respectively, compared to the corresponding original threshold values of 1800 and 90 μg/person per day. This confirms the applicability of the TTC values to substances relevant to food safety. Cramer Class II was excluded from our analysis because of containing too few compounds. Comparison with the Globally Harmonized System of classification confirmed that the Cramer classification scheme in the TTC approach is conservative for substances relevant to food safety.